Performativity and Evolutionary Signification of Plastics - Musto , Michela (E|C, 2023)
The evolving language mirrors societal shifts, with few materials influencing contemporary culture as profoundly as plastic. This material has reshaped daily life and entrenched habits, underscoring civilization as a construct of material existence. Plastic’s interplay with Earth’s ecosystem has defined us as material beings in a reciprocally performative relationship. J. A. Brandon’s 2019 Science Advances study, “Multidecadal increase in plastic particles in coastal ocean sediments”, highlights our era’s growing alignment with the so-called Plastic Age. In German, “Kunststoff” (plastic) suggests its artistic potential, a notion gaining prominence since the 1960s when plastic became central to mass consumption and disposable culture. Its pervasive influence extends beyond human environments to the entire ecosystem, spawning phenomena like artificial “islands”. This shift necessitates a reevaluation of humanity’s future coexistence with plastic. The material’s journey from valued to vilified demands exploration of its evolving semiotics, especially as we grapple with the natural-artificial symbiosis.